Food allergy competencies of dietitians in the United Kingdom, Australia and United States of America. Issue 1 (14th November 2014) - Maslin, Kate; Meyer, Rosan; Reeves, Liane; Mackenzie, Heather; Swain, Anne; Stuart‐Smith, Wendy; Loblay, Rob; Groetch, Marion; Venter, Carina
Abstract: Background: A knowledgeable and competent dietitian is an integral part of the food allergy multidisciplinary team, contributing to effective diagnosis and management of food allergic disorders. Little is currently known about the food allergy training needs and preferences of dietitians. The purpose of this paper is to measure and compare self‐reported food allergy competencies of dietitians based in the UK, Australia and USA. Methods: A survey of USA‐based paediatric dietitians was developed to measure self‐reported proficiency and educational needs in the area of food allergy. The survey was modified slightly and circulated online to paediatric and adult dietitians in the UK and Australia. Descriptive statistics and Pearson correlations are presented. Results: A total of 797 dietitians completed the questionnaire. Competency in "developing food challenge protocols" and "managing feeding problems" were rated the poorest overall across all three settings. A higher level of competency was significantly positively associated with length of practice as a dietitian, percentage of caseload composed of patients with food allergy and training in food allergy. The most popular topics for further training were food additives, pharmacological reactions and oral allergy syndrome. Conclusions: There is a need amongst dietitians to increase their knowledge in different aspects of food allergy diagnosis and management, specifically the areas of developing food challenge protocols and management of feeding problems. This study provides valuable information for designing targeted food allergy education for dietitians.